Dog man. Mothering heights - Pilkey, Dav, 1966-; Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2021)
The latest entry finds Dog Man tapping the strength of kindness and persistence when he is embroiled in a howling dilemma.
"Treehouse Comix proudly presents."
GN530L
Decoding demand: 78 (high) Semantic demand: 95 (very high) Syntactic demand: 56 (medium) Structure demand: 86 (very high)
Accelerated Reader AR
Keywords: Dogs -- Comic books, strips, etc; Police -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Action and adventure comics; Humorous comics; Graphic novels